COVID-19 leading to amputation in an eleven-year-old: A Case Report - Anam Zafar , Nahdia Zaman , Sonia Fazal, (Journal of Rawalpindi Medical College, 2021)
COVID-19 is an ongoing pandemic and all age groups are affected by SARS-CoV-2. Past studies showed that children are less affected by it and symptoms are quite variable as compared to adults. Multisystem Inflammatory Syndrome in Children (MIS-C) and Kawasaki-like illness are observed along with COVID-19 associated multi-organ failure, acute respiratory distress syndrome (ARDS), and coagulopathy in the paediatric age group. Thrombotic complications in patients with COVID-19 have variable presentation including venous thromboembolism and ischemic complications related to thrombosis of extremity, cerebral, coronary, and distal arteries. Early recognition of acute limb ischemia and treatment can help to reduce mortality and maximize the chance of limb salvage. Here, we report a case of 11 years old child who developed gangrene of bilateral lower limbs after mild COVID-19 illness that ended in below-knee amputation.